Cisco networking academy program : fundamentals of UNIX companion guide : focusing on Solaris and Linux - 448688 Myers, Dan; Lorenz, Jim; Cisco Systems, Inc.; Cisco Networking Academy Program (Indianapolis, IN : Cisco Press, 2004)
57